Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Keywords: archaeology; business & economics; economic history; history / ancient / general

Port of trade - Möller, Astrid (The Encyclopedia of Ancient History, 2013)
A “port of trade” is a theoretical concept developed by Karl Polanyi (1886–1964) to describe the phenomenon of a particular kind of trading post.
Keywords: anthropology; economic history; multiculturalism

Nature and Power - Radkau, Joachim (Social Science History, 2013)
Nature and Power is to be understood not only as human power against nature but also as power by nature in the sense of Michel Foucault's biopouvoir (biopower) or Francis Bacon's "Naturae non imperator nisiparendo" (Only by obeying nature may we dominate nature). The fragile human attempts to get power over nature and by nature have a long history, reaching back over millennia until prehistoric times, and much of world history may be explained in part by the unstable relationship between humans and nature. The environmental approach offers afresh look at global history. The great change that has happened in modern times seems to have been described best by Karl Polanyi (1944) in his Great Transformation, which also refers to a revolution in the human relation to nature. There are primeval symbioses of humans and nature that are the basis of environmental history until modern time. A global history of the environment may be written for a long time along the three great commons of history: woodlands, water, and pasture. The dark tune of Garrett Hardin's (1968) "Tragedy of the Commons," to be sure, does not dominate the whole melody of environmental history. There is also a lot of historical evidence for Elinor Ostrom's rehabilitation of the commons. But it is better to be cautious with dogmatic theories and sweeping judgments. In modern times Hardin may be right, at least in this or that regard. Ostrom's concept applies only to local, not to global commons. The underlying philosophy of Nature and Power is neither optimism nor pessimism but possibilism.
Keywords: BACON, Francis, 1561-1626; FOUCAULT, Michel, 1926-1984; Nature & Power: A Global History of the Environment (Book); POLANYI, Karl, 1886-1964; RADKAU, Joachim; environmental history; environmentalism; nature and civilization